CO2 capture by chemical absorption in coal-fired power plants: Energy-saving mechanism, proposed methods, and performance analysis. (August 2015) - Zhang, Guoqiang; Yang, Yongping; Xu, Gang; Zhang, Kai; Zhang, Dongke
Highlights: The energy-saving mechanism in CO2 capture by chemical absorption is analyzed. Energy-saving potential in typical CO2 capture process is quantified. Proposed methods decrease energy consumption of CO2 capture by 8.7–9.3%. The whole system analysis indicates a net efficiency rise of 0.91–1.26% points. Abstract: In an effort to minimize the efficiency penalty due to CO2 capture in coal-fired power plants, the mechanism and potential of energy saving in chemical absorption CO2 capture process were analyzed, and two methods of waste heat recovery in CO2 capture process were proposed. A thermodynamic model of the CO2 capture process was derived, through which the exergy destruction distributions were analyzed and the exergy destruction avoidable potential was quantified. Parameters optimization and wasted heat recovery in CO2 capture process were shown to have significant energy-saving potential. As to waste heat recovery, two methods were proposed, viz, Case 1: by introducing an organic power cycle; and Case 2: by compression of stripped stream for feed water preheating and steam generation. Process simulations using Aspen Plus demonstrated that equivalent work consumption was reduced by 9.32% in Case 1 and by 8.71% in Case 2 in comparison with the base case. The efficiency penalties for cases 1 and 2 in the coal-fired power plant were 9.39% and 9.45%, respectively, 0.97% and 0.91% lower than that for the base case. When the effect of steam bleeding on the flow characters of the low-pressure steam turbine was considered, the efficiency penalties of the two cases were 10.57% (Case 1) and 10.28% (Case 2), respectively, which are 0.97% and 1.26% lower than that of the base case. Waste heat recovery was shown to play a significant role in reducing the additional energy consumption due to CO2 capture, and the proposed cases provided effective heat recovery methods for coal-fired power plants with CO2 capture.